Semantic Changes in Generation Z Slang on TikTok - Mawarni, Kherin Nisa Ayu; Markhamah, M (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
The slang that appears on the social media platform TikTok comes from various sources, such as regional languages, foreign languages, or puns derived from Indonesian itself. Its forms and meanings vary, depending on the context of the video post. Slang used in the Fyp (For You Page) feature or posts on TikTok has the potential to become more popular than on other platforms. This study aims to describe the forms and types of changes in the meaning of Generation Z slang vocabulary found in posts on the social media platform TikTok. This study uses a qualitative descriptive method that collects descriptive data in the form of vocabulary. The data collection technique used in this study is the observation and note-taking technique. The researcher observed and recorded words that underwent changes in meaning found in posts on TikTok. Based on the research conducted, various forms and types of meaning changes were found. The results of the study found 12 slang vocabulary words consisting of: 2 words undergoing generalization, 2 words undergoing specialization, 5 words undergoing amelioration, 2 words undergoing pejorative changes, and 1 word undergoing association. The 12 findings contribute to the systematic mapping of semantic changes in slang language in the digital world, provide empirical understanding of meaning changes in Generation Z language on social media, and enrich contemporary linguistic studies.